2014
DOI: 10.2166/wst.2014.466
|View full text |Cite
|
Sign up to set email alerts
|

Commercial microwave links instead of rain gauges: fiction or reality?

Abstract: Commercial microwave links (MWLs) were suggested about a decade ago as a new source for quantitative precipitation estimates (QPEs). Meanwhile, the theory is well understood and rainfall monitoring with MWLs is on its way to being a mature technology, with several well-documented case studies, which investigate QPEs from multiple MWLs on the mesoscale. However, the potential of MWLs to observe microscale rainfall variability, which is important for urban hydrology, has not been investigated yet. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 18 publications
0
45
0
Order By: Relevance
“…More recently, commercial microwave links have been used to estimate the spatial and temporal rainfall variability (Leijnse et al, 2007;Fencl et al, 2015Fencl et al, , 2017. Rainfall estimates are obtained from the attenuation of the signal caused by rain along microwave link paths.…”
Section: Rainfall Estimationmentioning
confidence: 99%
“…More recently, commercial microwave links have been used to estimate the spatial and temporal rainfall variability (Leijnse et al, 2007;Fencl et al, 2015Fencl et al, , 2017. Rainfall estimates are obtained from the attenuation of the signal caused by rain along microwave link paths.…”
Section: Rainfall Estimationmentioning
confidence: 99%
“…This is consistent with the findings of Schleiss and Berne [16], who suggested that varying W t according to the rainfall pattern improves the accuracy of the rainfall detection rates under clear sky and rainy conditions. Fencl et al [25] applied a W t of 60 min (before rainfall) and 180 min (after rainfall) to eliminate the potential influence of attenuation by antenna wetting. Leijnse et al [33] showed that the effect of the shift in the A clear is seen to be major, especially for a long-lasting and low-intensity event.…”
Section: Detection Of Rain and Dry Spellsmentioning
confidence: 99%
“…Rainfall intensity distributions were then reconstructed from seven cellular microwave links that have lengths of 1-17 km and operate at frequencies of 8-23 GHz [12]. Fencl et al [25] investigate the effects of different topologies of microwave link networks on the retrieved spatio-temporal rainfall dynamics over an urban catchment and reported that most microwave links capture microscale rainfall variability very well. Barthès and Mallet [26] used Ku-band microwave sources on geostationary satellites to estimate rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Just recently, Fencl et al (2015) have mentioned a similar approach, also using a custom data acquisition software running within an operational CML network. In contrast to the software that we are presenting here, which handles multiple parallel requests of CML data, their software is only capable of serial data acquisition.…”
Section: State-of-the-art CML Data Acquisition For Researchmentioning
confidence: 99%